Combinational Immunotherapy for Hepatocellular Carcinoma: Radiotherapy, Immune Checkpoint Blockade and Beyond - Lee, Yun Hua; Tai, David; Yip, Connie; Choo, Su Pin; Chew, Valerie (Frontiers in Immunology, 2020)
The systemic treatment landscape for advanced hepatocellular carcinoma (HCC) has experienced tremendous paradigm shift towards targeting tumour microenvironment (TME) following recent trials utilizing immune checkpoint blockade (ICB). However, limited success of ICB as monotherapy mandates evaluation of combination strategies incorporating immunotherapy for improved clinical efficacy. Radiotherapy (RT) is an integral component in treatment of solid cancers, including HCC. Radiation mediates localized tumour killing and modify TME potentiating the action of ICB. Several preclinical and clinical studies have explored the efficacy of combining RT and ICB in HCC with promising outcomes. Greater efforts are required in discovery and understanding of novel combination strategies to maximize clinical benefit with tolerable adverse effects. This current review provides a comprehensive assessment of RT and ICB in HCC, their respective impact on TME, the rationale for their synergistic combination, as well as the current potential biomarkers available to predict clinical response. We also speculate on novel future strategies to further enhance the efficacy of this combination.